2017
DOI: 10.1186/s40317-016-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passive integrated transponder (PIT) implantation on Pacific lamprey ammocoetes

Abstract: Background: Little is known of the larval biology of Pacific lamprey (Entosphenus tridentatus), a species of conservation concern. With miniaturization of passive integrated transponder (PIT) tags, researchers now have the potential to individually mark larval lamprey. However, recent studies with sea lamprey (Petromyzon marinus) ammocoetes indicated that mortality was unacceptably high after surgical implantation of these tags. We examined survival, tag retention, growth, and swimming performance of Pacific l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
(48 reference statements)
3
14
0
Order By: Relevance
“…Although this process appears to allow smaller individuals to be tagged, the process may be too complicated for use in the field and a 135-mm threshold was suggested when following the simpler tagging procedure to implant 9-mm tags [20]. Low survival was observed for larval sea lamprey with an average length under 120 mm even with 8-mm tags (40% survival) and 9-mm tags (10% survival; [22]); however, recent research demonstrated substantially higher survival rates (97% field; 94% laboratory) for larval Pacific Lamprey implanted with 8.4 mm × 1.4 mm FDX PIT tags [23]. Schreck et al [18] suggested 150 mm as a minimum size using 8-mm PIT tags; our findings suggest this may be conservative as 82.3% of lamprey in our study <150 mm survived with larger tags (12 mm × 2.12 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this process appears to allow smaller individuals to be tagged, the process may be too complicated for use in the field and a 135-mm threshold was suggested when following the simpler tagging procedure to implant 9-mm tags [20]. Low survival was observed for larval sea lamprey with an average length under 120 mm even with 8-mm tags (40% survival) and 9-mm tags (10% survival; [22]); however, recent research demonstrated substantially higher survival rates (97% field; 94% laboratory) for larval Pacific Lamprey implanted with 8.4 mm × 1.4 mm FDX PIT tags [23]. Schreck et al [18] suggested 150 mm as a minimum size using 8-mm PIT tags; our findings suggest this may be conservative as 82.3% of lamprey in our study <150 mm survived with larger tags (12 mm × 2.12 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Previous field studies of PIT tagged lamprey have been limited to the detection of ammocoetes or lamprey that had begun to metamorphose using portable detection equipment that can be slowly and repeatedly passed over an area [17,22]. Although shorter lamprey can be successfully tagged with 8.4-mm PIT tags [23], detection range is generally reduced as tag size decreases [12]. To effectively detect outmigrating sea lamprey, studies should utilize the largest tags possible to maximize the probability of detection when using stream-spanning wire arrays.…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with all research efforts that involve attaching devices to animals, researchers must make every effort to minimize the adverse effects of equipping animals with PIT tags. There are numerous studies of the effects of PIT tags on survival and behavior, with most of this research focused on fish (Keck, 1994;Low et al, 2005;Nicolaus et al, 2008;Burdick, 2011;Thorstad et al, 2013;Guimaraes et al, 2014;Ratnayake et al, 2014;Moser et al, 2017;Schlicht and Kempenaers, 2018). The vast majority of these studies conclude that the effect of implanted PIT tags is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Passively integrated transponder tags (PIT tags) have been used to track individual movements in a wide range of aquatic and terrestrial animals (e.g. Gray, Killion, Roloff, Dotters, & Engstrom, 2016;Hua, Jiao, Neves, & Jones, 2015;Moser, Jackson, Mueller, Maine, & Davisson, 2017;O'Donnell, Thompson, & Semlitsch, 2016). Passively integrated transponder-tag life is long-lasting (>10 years), which allows for long-term monitoring of animals, and PIT tags are relatively inexpensive.…”
Section: Introductionmentioning
confidence: 99%